Chlorophyll content of the hope mutant clones of Bogor taro (Colocasia esculenta (L.) Schott) - Hilda Izzatul Adibah; Febi Nurilmala; Ade Ayu Oksari (JURNAL SAINS NATURAL, 2021)
The development of the Bogor taro plant genetic variation with gamma-ray radiation has resulted in three mutant clones of the hope line with high carbohydrate and low calcium oxalate advantages. The carbohydrate content may correlate with chlorophyll content which plays a role in the photosynthesis process, so it is necessary to know the chlorophyll content in the mutant clones of the Bogor taro hope line and its relationship with its growth in two locations in Kemang District and Cijeruk District, Bogor Regency. The results showed that the mutant clones of the hope line B1023 planted in Kemang District had higher chlorophyll content than the parents. Meanwhile, the mutant clones of the hope line B1511 planted in the Cijeruk District had higher chlorophyll content than the parents. The chlorophyll content of the hope mutant clones planted in Kemang District was higher than the hope mutant clones planted in Cijeruk District. High chlorophyll content showed a negative relationship with tuber wet weight and carbohydrate content but did not affect the number of leaves and tillersKeywords: Chlorophyll a, chlorophyll b, fotosyntesis, mutant clone, Colocasia esculentaABSTRAKKandungan  klorofil dan pertumbuhan pada klon mutan galur harapan tanaman talas Bogor (Colocasia esculenta (L.) Schott)Pengembangan variasi genetik tanaman talas Bogor dengan radiasi sinar gamma telah menghasilkan tiga klon mutan galur harapan dengan keunggulan tinggi karbohidrat dan rendah kalsium oksalat.  Kandungan karbohidrat mungkin berhubungan erat dengan kandungan klorofil yang berperan dalam proses fotosintesis, sehingga  perlu untuk diketahui kandungan klorofil pada klon mutan galur harapan tanaman talas Bogor dan hubungannya dengan pertumbuhannya di dua lokasi Kecamatan Kemang dan Kecamatan Cijeruk Kabupaten Bogor.  Hasil penelitian menunjukkan bahwa klon mutan galur harapan B1023 yang ditanam di Kecamatan Kemang memiliki kandungan klorofil lebih tinggi dari tetua. Sedangkan pada klon mutan galur harapan B1511 yang ditanam di Kecamatan Cijeruk memiliki kandungan klorofil lebih tinggi dari tetua. Kandungan klorofil klon mutan galur harapan yang ditanam di Kecamatan Kemang lebih tinggi dibandingkan dengan kandungan klorofil klon mutan harapan yang ditanam di Kecamatan Cijeruk. Kandungan klorofil tinggi menunjukkan hubungan negatif dengan bobot basah umbi dan kandungan karbohidrat, tetapi tidak memberikan pengaruh terhadap jumlah daun dan anakan. Kata kunci :  Klorofil a, Klorofil b, Fotosintesis, Klon mutan, Colocasia esculenta